2017
DOI: 10.1038/sj.bdj.2017.665
|View full text |Cite
|
Sign up to set email alerts
|

Caries risk/susceptibility assessment: its value in minimum intervention oral healthcare

Abstract: This narrative review describes the intimate connection between minimum intervention (MI) oral healthcare and caries risk/susceptibility assessment (CRA). Indeed CRA is the corner stone of an MI care plan, allowing the determination of the appropriate interventions (non-invasive as well as invasive [restorative]) and recall consultation strategies. Various CRA protocols/models have been developed to assist the oral healthcare practitioner/team in a logical systematic approach to synthesising information about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 36 publications
0
41
0
5
Order By: Relevance
“…We found that three categories performed better than five for caries prediction in the present population. In the original Cariogram manual, five risk categories are advocated, but in general practice, three levels (low, moderate, high) seem more common . For the country setting, the “standard set” was selected according to the manual as the “most suitable setting for an industrialized country without water fluoridation”, like Greece.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that three categories performed better than five for caries prediction in the present population. In the original Cariogram manual, five risk categories are advocated, but in general practice, three levels (low, moderate, high) seem more common . For the country setting, the “standard set” was selected according to the manual as the “most suitable setting for an industrialized country without water fluoridation”, like Greece.…”
Section: Discussionmentioning
confidence: 99%
“…In the original Cariogram manual, five risk categories are advocated, 5 but in general practice, three levels (low, moderate, high) seem more common. 2 For the country setting, the "standard set" was selected according to the manual as the "most suitable setting for an industrialized country without water fluoridation", like Greece. Concerning the "group setting" only one study 26 has used "high set" for Cariogram calculation but this was for a special group of mentally challenged and visually impaired individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Different caries risk assessment models have been developed to help dental professionals assess patients' caries risk. 2 While many dentists apparently do some type of informal caries risk assessment, there remains the need for broadly adopted ideally electronic caries risk assessment tools that can help dental professionals in establishing and documenting the caries risk status of their patients as well as tracking changes over time. …”
Section: Caries Risk Assessment Toolsmentioning
confidence: 99%